Advance Directives: Knowledge of the Topic Among Psychiatrists - Domingues, Vania Novelli; Castro, Luísa; Monteiro, Monica Domingues; Cordero da Silva, José Antonio; Rego, Francisca; Rego, Guilhermina (Frontiers in Public Health, 2022)
Objective: Advance directives are becoming increasingly important as health technologies evolve. We sought to assess psychiatrists’ knowledge of advance directives, as this knowledge is fundamental to the implementation and drafting of these personal documents. Methods: A previously published questionnaire that evaluated the knowledge of medical professors was used. The sample, composed of psychiatrists from Rio de Janeiro, Brazil, originated from a publicly available list. During the search process, the COVID-19 pandemic affected Brazil and the rest of the world, which influenced our methodology and results. Results: A total of 40 psychiatrists participated in the study. The results obtained, although not significant, suggested that psychiatrists with an increased time of practice had more knowledge of advance directives. Nevertheless, less than half of the participants had knowledge about this topic. Conclusion: The number of psychiatrists surveyed indicates the need for further studies on the subject. The influence of the COVID-19 pandemic on this study led to findings such as a change in sensitivity when addressing the topic and greater difficulty in contacting professionals.